Integrated Student Health Week: a humanizing experience in the context of remote education (Research, Society and Development, 2020)
The present work addresses a project aimed at students at the Federal Institute of Goiás, based on humanizing education and the development of socioemotional skills in the struggle of the Covid-19 pandemic. Aiming to discuss relevant topics on coping with the pandemic, providing encouragement, welcome and a sense of belonging to students, in order to bring comfort and help mitigate the effect of the undesirable consequences of social isolation, a project was created entitled: “Week Integrated Student Health”. A qualitative research was chosen, of a descriptive-exploratory nature, for the elaboration of the experience report, based on a bibliographic review for the foundation of the theoretical framework. It is concluded that the objectives of the project were achieved, due to the number of participations and interactions in synchronous and asynchronous activities, as well as by the reports presented by the students. It is clear that initiatives such as the Integrated Student Health Week should be encouraged, so that students can take on dialogue channels, interaction and acceptance with the academic community of which they are a part.